Analysis of Supplement Consumption of Pregnant Women with Orofacial Cleft in Children at RSAB Harapan Kita Jakarta - Sani, Shofiyyah Najihan; Tanziha, Ikeu; Ekayanti, Ikeu; Hak, Muhammad Syafudin (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Congenital abnormalities remain a leading cause of death in toddlers, with a global death rate of 8.7 per 1000 live births in 2016. Cleft lip, a congenital birth defect, has an incidence rate in Indonesia that increases by an average of 7,500 cases per year. One of the exogenous factors influencing the occurrence of orofacial clefts (OFC) is maternal supplement intake. This study aimed to assess the relationship between maternal supplement consumption and the incidence of OFC in children and identify the dominant factors in maternal supplement intake. The study employed an observational analytic method with a case-control approach, involving 70 maternal samples calculated using the Lemshow formula. Data for the case group were obtained from mothers who underwent treatment at RSAB Harapan Kita Jakarta. The sampling method used was non-probability convenience sampling, and the data were analyzed using univariate, bivariate, and multivariate methods. The results showed a tendency for supplement consumption and maternal zinc requirements to increase the risk of OFC in children. However, a significant relationship was found between the timing of supplement consumption and the adequacy of folic acid, Vitamin B6, and Vitamin B12 supplements. In the multivariate analysis, the dominant risk factors were the need for folic acid and zinc in mothers. Based on the study results, it is recommended that local government regulations consider these factors to optimize the management and prevention of non-syndromic OFC in children, especially in Jakarta.